Improving Students' Achievement in Geometry Through Laboratory-Based Instructional Methods in Jalingo Metropolis, Taraba State, Nigeria - Ajai, John; Ogungbile, Titilayo (Papanda Publisher, 2025)
This study investigated the effect of laboratory-based instructional methods on students' achievement in geometry within the educational context of Jalingo Metropolis, Taraba State, Nigeria, over six weeks. Recognising the potential of hands-on, experiential learning approaches in mathematics education, particularly in geometry, this research explored the effectiveness of laboratory-based instruction in enhancing student performance. Guided by three research questions and hypotheses, the quasi-experimental research design was employed on a sample of 160 Upper Basic II students, through pre-and post-test assessments. The Geometry Achievement Test (GAT) with a reliability index of 0.91 for the GAT, determined using the K-R20 method, was used for data collection. The mean and standard deviation statistics were employed to answer the three research questions, while covariance (ANCOVA) analysis was employed to test all hypotheses at a significance level of 0.05. The study found a significant improvement in geometry achievement among students exposed to the laboratory-based method, with 56% of the achievement score variance attributed to this method. Additionally, it identifies a noteworthy difference in achievement scores between male and female students taught geometry using the laboratory-based approach, with a significant interaction between the teaching method and gender. These findings underscore the potential of laboratory-based instructional methods to improve student engagement and comprehension in geometry, particularly in educational settings that face similar resource and teaching challenges. By fostering hands-on learning and critical thinking, this approach could be an effective strategy for enhancing math achievement and supporting curriculum development in Nigeria and comparable regions. Overall, the study contributes valuable insights to the discourse on innovative pedagogical practices in mathematics instruction, offering guidance for educators and policymakers aiming to improve mathematics education in similar contexts.